Efficacy of Bleaching Agents on Color and Micro Hardness of SDF Treated Primary Teeth - Somia M. Selim,; Mohammed H. Mostafa,; Shaymaa A. El Shishiny, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Bleaching agents affect color, microhardness, and esthetic balance in enamel. Context: Dental caries remains a significant health issue. Silver Diamine Fluoride (SDF) is effective in arresting caries but causes tooth discoloration. Bleaching agents may mitigate discoloration but could impact enamel properties. Aims: This study evaluates the effects of bleaching agents on the color and microhardness of SDF-treated demineralized primary tooth enamel. Settings and Design: An in vitro study conducted on 40 extracted human primary anterior teeth Methods and Material: Teeth were treated with SDF and divided into four groups: Potassium Iodide (KI), Hydrogen Peroxide (HP), Carbamide Peroxide (CP), and a combination of KI+CP. Color changes were measured using a spectrophotometer, and microhardness was tested using the Vickers Microhardness method. Statistical analysis used: Data were analysed using ANOVA and Tukey’s post hoc test with significance at P ≤ 0.05. Results: All agents improved lightness (L) and reduced discoloration. CP caused significant microhardness reduction, while KI+CP had minimal impact. Conclusions: Bleaching agents are effective in reducing SDF-induced discoloration, but their effects on enamel microhardness vary